2016
DOI: 10.1038/jhh.2016.77
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-visit blood pressure variability, average BP level and carotid arterial stiffness in the elderly: a prospective study

Abstract: In a cross-sectional study, visit-to-visit blood pressure (BP) variability was shown to be associated with artery remodelling. Here, we investigated the impact of visit-to-visit BP variability and average BP on the carotid artery remodelling progression in high-risk elderly according to different classes of antihypertension medication use/non-use. BP measurements and carotid ultrasound were performed in the common carotid artery in 164 subjects (mean age 79.7 years at baseline, 74.7% females) with one or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In this regard, a cross-sectional study of elderly patients with at least one risk factor for cardiovascular disease showed an association between carotid arterial stiffness, high average systolic blood pressures and high visit-to-visit systolic blood pressure 23 . In another clinical study, increased aortic stiffness (measured by pulse wave velocity) correlated significantly with negative end organ effects in the heart and kidney in patients with mild hypertension 24 .…”
Section: Clinical Relevancementioning
confidence: 99%
“…In this regard, a cross-sectional study of elderly patients with at least one risk factor for cardiovascular disease showed an association between carotid arterial stiffness, high average systolic blood pressures and high visit-to-visit systolic blood pressure 23 . In another clinical study, increased aortic stiffness (measured by pulse wave velocity) correlated significantly with negative end organ effects in the heart and kidney in patients with mild hypertension 24 .…”
Section: Clinical Relevancementioning
confidence: 99%
“…25 In elderly hypertensive patients, the BP variability is also reported as a risk factor for mortality 26,27 and cardiovascular death 28 and a predictor of arterial stiffness progression. 29 Our conclusion that the SPC of Cil/Val reduces age-related increased home BP variability may have clinical significance. This benefit needs to be confirmed in the future.…”
Section: Discussionmentioning
confidence: 72%
“… 12 During the mean follow‐up period of 4.2 years, VVV SBP had a significant positive association with the change of carotid stiffness parameter β. 12 In the coronary artery risk development in young adults (CARDIA) study, 13 the association between VVV SBP and 10‐year percent change in arterial stiffness was investigated among 1122 middle‐aged individuals without antihypertensive medications. In a multiple linear regression analysis, the group with the highest quintile of VVV SBP had a higher decline in the distensibility coefficient as well as a higher progression in Young's elastic modulus compared with those in the lowest quintile of VVV SBP independently of average SBP level.…”
mentioning
confidence: 87%